2019
DOI: 10.1128/jcm.01420-19
|View full text |Cite
|
Sign up to set email alerts
|

False-Positive Results for Human Immunodeficiency Virus Type 1 Nucleic Acid Amplification Testing in Chimeric Antigen Receptor T Cell Therapy

Abstract: Chimeric antigen receptor (CAR) T cell immunotherapy has been a major advancement in cancer therapeutics. Reprogramming of T cells is achieved by using gammaretroviral or lentiviral vectors, which may interfere with human immunodeficiency virus type 1 (HIV-1) nucleic acid amplification testing (NAAT). Here, we describe three clinical scenarios in which CAR T cell immunotherapy interfered with HIV-1 testing, including (i) routine infectious disease screening prior to stem cell transplantation in a 16-year-old f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Nevertheless, our findings (patients #2 and #4) show the loss of completed chimerism observed in the CD19 + cells subset could be associated with a higher risk of relapse, even if not accompanied by a loss of CD19 + lymphocyte aplasia or a significant decrease in HIV viral load (patient #2), being the last one an indirect biomarker which could associate cross-reactions with HIV infection, leading to false-positive results ( 13 15 ). Although there is not enough evidence on optimal treatment in this case, our findings, supported by other publications ( 16 ), suggest that DLI may be not as effective as in other settings ( 17 ).…”
Section: Resultsmentioning
confidence: 73%
“…Nevertheless, our findings (patients #2 and #4) show the loss of completed chimerism observed in the CD19 + cells subset could be associated with a higher risk of relapse, even if not accompanied by a loss of CD19 + lymphocyte aplasia or a significant decrease in HIV viral load (patient #2), being the last one an indirect biomarker which could associate cross-reactions with HIV infection, leading to false-positive results ( 13 15 ). Although there is not enough evidence on optimal treatment in this case, our findings, supported by other publications ( 16 ), suggest that DLI may be not as effective as in other settings ( 17 ).…”
Section: Resultsmentioning
confidence: 73%
“…CAR-T cells were usually assessed by flow cytometry, using the CAR Detection Reagents (Miltenyi), and by quantitative polymerase chain reaction (qPCR) using an assay commercialized to quantify HIV-1 (Generic HIV DNA Cell â test for research use, Biocentric, Bandol, France). 10,11 These two assays performed similarly (r = 0Á6782, P < 0Á0001 by Spearman correlation; n = 44; Fig 1A and Figure S1). Over a broad range of frequencies from 0Á12 to 22% CD3 + CAR-T cells, we showed that, for the detection of CAR-T cells, results obtained with our 106/116 Cd-anti-biotin CD19Fc used for mass cytometry strongly correlated with those obtained by flow cytometry (Pearson correlation; r = 0Á95, P < 0Á05; n = 72; confirmed by the validation method of Bland-Altman; Fig 1B).…”
Section: Development and Robustness Of A Mass Cytometry Customized Pa...mentioning
confidence: 65%
“…Therefore, we customized the Maxpar panel by developing a cadmium ( 106/116 Cd)–anti‐biotin CD19Fc (106/116 cadmium metal isotopes, Fluidigm, Canada; pure anti‐biotin antibody and CD19Fc Detection Reagent, biotin, Milteny Biotec, Bergisch Gladbach, Germany) that identify CAR‐T cells and validated its robustness by comparison with routine assays. CAR‐T cells were usually assessed by flow cytometry, using the CAR Detection Reagents (Miltenyi), and by quantitative polymerase chain reaction (qPCR) using an assay commercialized to quantify HIV‐1 (Generic HIV DNA Cell ® test for research use, Biocentric, Bandol, France) 10,11 . These two assays performed similarly ( r = 0·6782, P < 0·0001 by Spearman correlation; n = 44; Fig 1A and Figure S1).…”
Section: Development and Robustness Of A Mass Cytometry Customized Pa...mentioning
confidence: 90%
“…Recently, in HIV-1 seronegative cancer patients under chimeric antigen receptor (CAR) T-cell immunotherapy, it has been described false HIV-1 nucleic acid amplification with a double-targets assay different from Aptima ( 16 , 17 ). This was attributed to the detection of LTR elements present in lentiviral vectors used in this type of immunotherapy ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%